2002
DOI: 10.1053/rapm.2002.35163
|View full text |Cite
|
Sign up to set email alerts
|

Epidural blockade suppresses lipolysis during major abdominal surgery☆

Abstract: Epidural block suppresses lipolysis during and 2 hours after major abdominal surgery without affecting plasma glycerol or FFA concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…20 Our previous analysis of Medicare patients undergoing total-hip replacement also did not demonstrate any benefit of postoperative epidural analgesia in decreasing 7-day or 30-day mortality. 10 Whether the many physiologic benefits of epidural analgesia 8,9,[21][22][23][24][25][26] contributed to a decrease in postoperative mortality is unclear, as we did not find a decrease in the perioperative morbidities that we examined. Subgroup analysis in the Cooperative Overview of Randomized Trials of Regional Anesthesia metaanalysis showed that neuraxial block decreased the odds of deep-vein thrombosis by 44%, pulmonary embolism by 55%, transfusion requirements by 50%, pneumonia by 39%, and respiratory depression by 59%.…”
Section: Discussionmentioning
confidence: 96%
“…20 Our previous analysis of Medicare patients undergoing total-hip replacement also did not demonstrate any benefit of postoperative epidural analgesia in decreasing 7-day or 30-day mortality. 10 Whether the many physiologic benefits of epidural analgesia 8,9,[21][22][23][24][25][26] contributed to a decrease in postoperative mortality is unclear, as we did not find a decrease in the perioperative morbidities that we examined. Subgroup analysis in the Cooperative Overview of Randomized Trials of Regional Anesthesia metaanalysis showed that neuraxial block decreased the odds of deep-vein thrombosis by 44%, pulmonary embolism by 55%, transfusion requirements by 50%, pneumonia by 39%, and respiratory depression by 59%.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, the addition of regional to general anesthesia, with its demonstrated benefits in adult and pediatric patients undergoing major surgery, is receiving increasing attention from anesthetists and cardiac surgeons. [2][3][4][5][6][7] Regional anesthesia may attenuate adverse physiologic stress responses associated with cardiothoracic surgery, including alterations in circulatory (tachycardia, hypertension, vasoconstriction), metabolic (increased catabolism and cortisol release), immunologic (impaired immune response), and hemostatic (platelet activation) systems. 8 -12 Two recent randomized, controlled trials 3,4 have investigated the potential benefits of thoracic epidural anesthesia in patients undergoing conventional CABG with cardiopulmonary bypass (CPB) and cardioplegic arrest.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of statistically significant differences in the incidence of vasodilator support (either intra-or (7, 21) 7.5 (7,10) Missing data are minimal (Ͻ 10%). CCS ϭ Canadian Cardiovascular Society; CVA ϭ cerebral vascular accident; GA ϭ general anesthesia only; GAE ϭ general anesthesia plus epidural; IQR ϭ interquartile range; NYHA ϭ New York Heart Association; TIA ϭ transient ischemic attack.…”
Section: Secondary Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…An elegant series of investigations in patients undergoing open colon surgery indicates that a combination of epidural anesthesia and analgesia in conjunction with nutrition maximizes the perioperative preservation of normal protein catabolism, muscle mass, lipolysis, and glucose metabolism compared with systemic opioids. [36][37][38] All of these factors (better perioperative analgesia, reduction in fatigue, attenuated postoperative catabolism and muscle loss, reduced deconditioning) probably explain the improved postoperative quality of life observed in the epidural analgesia group.…”
Section: Postoperative Carementioning
confidence: 99%